Paparan Penyelaman Subkronik Memodulasi Profil Eritrosit dan Lipid Darah pada Tikus Wistar - Putro, Helen Eko; Torop, Epa Yohana Toga; Fitria, Laksmindra; Mulyati; Rahadian Yudo Hartantyo (Berkala Ilmiah Biologi, 2026)
Voluntary diving exercise refers to the behavior of voluntarily swimming underwater for a specific distance and duration. Diving places the body in a hypoxia state, which modulates the regulation of hematopoiesis and lipid metabolism. The effects of repeated voluntary diving exposure over a subchronic period on erythrocyte profiles and blood lipid levels in rats remain largely unknown. This study aims to investigate the effects of subchronic voluntary diving exercise on erythrocyte profiles and blood lipid levels in rats. Twenty female Wistar rats were divided into a diving group (SL) and a control group (KN). The treatment group underwent diving for 60 days, with a frequency of five training days and two rest days per week. The control group performed swimming activities over the same distance without diving and followed the same schedule. Blood samples were collected on days 0, 30, and 60 for erythrocyte profile analysis, blood plasma was collected to analyze blood lipid profile. At the end of the treatment period, the animals were euthanized and a necropsy was performed. The spleens were collected and weighed using an analytical balance. On day 60, the red blood cell count, hemoglobin, and hematocrit in the treatment group were lower than those in the control group, accompanied by increases in MCH and MCHC. These findings indicate that there were fewer circulating red blood cells but with a higher hemoglobin content per cell. These changes, along with the increase in spleen weight, indicate a physiological response to diving exposure involving the spleen and are likely related to erythrocyte redistribution (splenic sequestration). Additionally, the decrease in LDL accompanied by an increase in HDL indicates a more protective lipid profile in rats as a metabolic adaptation. Subchronic voluntary diving exercise in rats triggers physiological adaptations in the form of changes in the erythrocyte profile, increased spleen weight, and an improved lipid profile in response to repeated hypoxia exposure.